An Investigation into Psychological Safety and Productivity of Teacher Educators - Yinn Mar Saw; Su Myat Aye (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The main purpose of this study was to investigate the impact of teacher educators’ psychological safety on their productivity. A quantitative research approach was employed. A total of 1,040 teacher educators from three education universities and eighteen education degree colleges participated in the study, and a simple random sampling technique was used to select the participants. The findings revealed that the teacher educators' level of psychological safety was above average. The results of the one-way analysis of variance (ANOVA) indicated that there were significant differences in psychological safety based on teaching experience and academic qualification. The findings also indicated that the teacher educators' productivity was high. The independent-samples t-test revealed that teacher educators' research experience was significantly related to their productivity, with teacher educators who have research experience have higher productivity than teacher educators who don’t have research experience. Moreover, the results of the one-way analysis of variance (ANOVA) indicated that there were significant differences in productivity based on teaching experience and academic qualification. Furthermore, the results of the correlation analysis showed that teacher educators' psychological safety was positively associated with their productivity. Multiple regression analysis further revealed that psychological safety was a significant predictor of teacher educators' productivity, accounting for 11.8% of the variance in productivity.